1975
DOI: 10.1016/0370-2693(75)90288-9
|View full text |Cite
|
Sign up to set email alerts
|

Chemical effects in the capture of negative muons

Abstract: Muonic Lyman-series x~ray spectra have been measured for several isoelectronic and isostructural molecular series and related pure elements. Seven muonic Iurman series lines were observed from liquid argon with relative intensities consistent with neighboring isoelectronic ions, but in stark contrast. to the single line previously reported for a gaseous argon target. The measured relative capture •rates and Lyman intensity correlations provide new evidence for chemical structure influences on the capture of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1977
1977
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Most of the older [2][3][4][5] and more recent experiments [12][13][14][15] did not agree with the Z law. The deviations appeared to be either with no correlation to known physical facts or to show a certain periodicity [13,16,17] with Z.…”
Section: )mentioning
confidence: 84%
“…Most of the older [2][3][4][5] and more recent experiments [12][13][14][15] did not agree with the Z law. The deviations appeared to be either with no correlation to known physical facts or to show a certain periodicity [13,16,17] with Z.…”
Section: )mentioning
confidence: 84%
“…This phenomenon has previously been interpreted as arising from molecular effects [5,6]. This investigation of molecular effects in the cascade process has, of necessity, been carried out using a cascade code based on the physics of pion capture in a single isolated atom.…”
Section: Discussionmentioning
confidence: 99%
“…In general, it has been found that the modified statistical distribution gives better agreement with the data than the statistical model, but even the former does not always lead to good agreement [6,11,12]. Condo [233 has observed that the modified statistical distribution with the same value of c~ should not be expected to fit both the relative and absolute X-ray yields, since only one parameter is available to allow for a variety of effects, such as distribution over n, uncertainty on the refilling rate and molecular effects.…”
Section: The Angular Momentum Distributionmentioning
confidence: 93%
“…The mesonic X-ray intensity pattems as well as the capture ratios are useful for studying these chemical effects because they are influenced by different environments [6][7][8][9], For example, Schneuwly et al have shown that boron nitride and carbon in cubic structures have different muonic X-ray intensity pattems from those in hexagonal stmctures [8], and O'Leary and Jackson have reported that the sugar isomers such as glucose and mannose have different pionic X-ray intensity pattems [9].…”
Section: Introductionmentioning
confidence: 98%